PENGARUH PEMBINAAN TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR PEKERJAAN UMUM PELAKSANAAN JALAN NASIONAL WILAYAH PROVINSI GORONTALO - Poppy Mu’jizat (AkMen JURNAL ILMIAH, 2020)
This study aims to determine the effect of coaching on employee performance at the Public Works Office for the Implementation of National Roads in Gorontalo Province either simultaneously or partially. Collecting main data is through a list of statements / questions tested through validity and reliability tests of each item of statement / question contained in the statement / question list. The analytical method used is path analysis by first converting the ordinal scale data to the interval scale. The object of this research is coaching, work performance. The results of the first hypothesis show that Coaching (X), namely Career Development (X1) and Discipline Development (X2) Education and Training Guidance (X3), simultaneously have a positive and significant effect on work performance at the Public Works Office for the Implementation of National Roads in Gorontalo Province area of ​​85 , 2%. Meanwhile, 14.8% is influenced by other variables not examined in the research model. The results of testing the second hypothesis show that Coaching (X), namely Career Development (X1) and Discipline Development (X2) Education and Training Guidance (X3), partially have a positive and significant effect on work performance at the Public Works Office for the Implementation of National Roads in Gorontalo Province sub Career Development variable (X1) partially has a positive and significant effect on Job Performance (Y) by 18.2%. Sub Discipline Development (X2) partially has a significant effect on Job Performance (Y) of 52.7%. Education and Training Sub Development (X3) partially has a significant effect on Job Performance (Y) by 32.2%.